Qual é o tempo certo? O uso de telas em crianças escolares - Fodra, Bruna Motta (Universidade Federal de São Carlos, 2023)
Recent research has shown changes in children’s screen time during the COVID-19 pandemic, and how it can potentially affect child development. It is important, however, to better understand parents' perspective on these possible changes, in particular, on the types of devices being used, their function, screen time, and parental control strategies. The goal of the present study was to obtain an understanding of parents' perspective on screen use during and after the period of social isolation. A form (Google form) was sent to parents including questions about the main devices being used, their assessment of them, average screen time, the type of activity done in each device, as well as their strategies to control time and content. Additionally, we explored how parents evaluate their children’s screen use. Results showed that there was an increase in children’s screen time during the pandemic, with a subsequent decrease. Participants can see both positive and negative aspects of screen use, with special interest on potential educational benefits. On the other hand, parents’ reports reveal a significant concern about possible negative effects of excessive screen use (e.g.. agitation, emotional instability). Additionally, almost all participants (96,9%) apply control and restriction measures for screen use, although many of them report important challenges of monitoring children’s screen time and content.
How much time is right? School-aged children's screen use
Keywords: Telas; Dispositivos eletrônicos; Atitudes parentais; Crianças; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO